2021
DOI: 10.1136/bmjopen-2020-042432
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Chinese version of medical maximizer-minimizer scale: a cross-sectional study

Abstract: ObjectiveMedical overutilisation and underutilisation affect optimal healthcare. The Medical Maximizer-Minimizer Scale (MMS) was developed to assess individual medical maximising and minimising tendencies. Despite significant improvement in the healthcare system over the past four decades, no psychometric scales to examine treatment maximising and minimising preferences are available in China. This study aimed to translate the MMS into Chinese and examine its reliability and validity in a Chinese population.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Reliability refers to the consistency and dependability of test results, ie., the degree to which test results are not affected by time, place, or other variables. 23 The results of this study showed that the two measurements were correlated, indicating that the C-OASES has stable repeatability. The results also imply that the C-OASES can be used as a reliable tool to measure the level of knowledge of STs among Chinese nurses.…”
Section: Discussionmentioning
confidence: 54%
“…Reliability refers to the consistency and dependability of test results, ie., the degree to which test results are not affected by time, place, or other variables. 23 The results of this study showed that the two measurements were correlated, indicating that the C-OASES has stable repeatability. The results also imply that the C-OASES can be used as a reliable tool to measure the level of knowledge of STs among Chinese nurses.…”
Section: Discussionmentioning
confidence: 54%